Pengaruh Motivasi dan Lingkungan Kampus terhadap Minat Berwirausaha Mahasiswa Pertanian di Polbangtan Yogyakarta Magelang - Annisa Wirrdiana Yuniasih; Hafidz Adnin Al Ghoza; Ridi Antyaningrum; Scantya Aulya Rahma; Wahyu Istiqomah; Nur Rohmah Lufti A'yuni (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
Unemployment is a severe problem for a country and has quite an enormous impact on the economic sector. The government must devise ways to address Indonesia's growing unemployment rate. The increasing number of unemployed in Indonesia requires the government to devise solutions to overcome this. An alternative that can be done is to increase the number of entrepreneurs by building an entrepreneurial spirit in prospective educated graduates. A survey must determine how interested students are in becoming entrepreneurs, particularly those in the Polbangtan Yogyakarta Magelang Agriculture Department. This will become a benchmark for entrepreneurship education at Polbangtan Yogyakarta Magelang in building entrepreneurial motivation in the campus environment. This study aimed to ascertain how students' interest in agricultural entrepreneurship was influenced by their campus environment and motivation at Polbangtan Yogyakarta Magelang. The research was conducted in October-November 2023 and used quantitative methods. The study's population comprised 132 students in the 2020 class from Polbangtan Yogyakarta Magelang's Department of Agriculture. Simple random sampling was employed to establish the sample, and 57 students who met the criteria using the Slovin formula were included. The method used is Multiple Linear Regression with t-test (partial), F-test (simultaneous), and coefficient of determination. The data analysis tool used SPSS 22.0 for Windows software. Equation Y = 2.351 + 0.500X1 + 0.422X2, with a coefficient of determination of 0.876, was displayed in the computation results. This means that 87.6% of the motivation variables (X1) and campus environment (X2) can show the entrepreneurial interest variable (Y), and other variables explain the remaining 12.4%. In light of the t-test and F-test findings, it was determined that the motivation and campus environment variables each significantly and simultaneously influenced students' interest in entrepreneurship in the agricultural sector.